(δ, γ)-Dunkl Lipschitz functions in the space L^2(R, |x|^2α+1dx)
Using a generalized Dunkl translation, we obtain an analog of Theorem 5.2 in Younis' paper [2] for the Dunkl transform for functions satisfying the (δ, γ)-Dunkl Lipschitz condition in the space L^2(R, |x|^2α+1dx).